Enhancement of the Wear Resistance and Microhardness of Aluminum Alloy by Nd:YaG Laser Treatment - Haitham T. Hussein; Abdulhadi Kadhim; Ahmed A. Al-Amiery; Abdul Amir H. Kadhum; Abu Bakar Mohamad (The Scientific World Journal)
Influence of laser treatment on mechanical properties, wear resistance, and Vickers hardness of aluminum alloy was studied. The specimens were treated by using Nd:YaG laser of energy 780 mj, wavelength 512 nm, and duration time 8 ns. The wear behavior of the specimens was studied for all specimens before and after treatment by Nd:YaG laser and the dry wear experiments were carried out by sing pinon-disc technique. The specimens were machined as a disk with diameter of 25 mm and circular groove in depth of 3 mm. All specimens were conducted by scanning electron microscopy (SEM), energy-dispersive X-ray florescence analysis (EDS), optical microscopy, and Vickers hardness. The results showed that the dry wear rate was decreased after laser hardening and increased Vickers hardness values by ratio of 2.4 : 1. The results showed that the values of wear rate for samples having circular grooves are less than samples without grooves after laser treatment.